Knowledge, Attitude, and Practices Regarding Safe and Hygienic Food among Food Handlers in some Benghazi Hospitals - Elsherif , Sara Ahmed; Mohammed , Aya Abdallah; Mansor , Budor Omar; Elbarghathi , Manar Wanis; Elmodabel , Najwa Faraj (Scientific Journal of University of Benghazi, 2024)
Background: In the healthcare sector, hospitals play a pivotal role in patient care, with food services being a vital component. Aim: This study focused on the knowledge, attitudes, and practices (KAP) of food handlers in some hospitals in Benghazi, Libya, who are instrumental in preventing foodborne illnesses through proper food safety and hygiene. Methods: A descriptive study of a cross-sectional design was conducted in Benghazi, the research assessed 70 food handlers from Benghazi Medical Center, Benghazi Children’s Hospital, and Dar-Alshifa Hospital, aged 18 to 48 years. Data was collected via interviews using a questionnaire covering socio-demographic information and KAP-related questions. Results: The participants, encompassing various roles such as waiters, cooks, nutritionists, and cleaners, mostly had 1-5 years of experience, with 58.6% having undergone prior training. Despite a generally positive attitude towards food safety, the study uncovered a deficiency in food hygiene knowledge. However, practices for periodic analysis were commendably executed. Further scrutiny indicated that knowledge levels regarding hygiene and sanitation did not significantly differ among food handlers based on age, gender, occupation, education, experience, training, or hospital type. Conclusion: The findings suggest that while the attitude towards food safety is commendable, there is an imperative need to enhance the food handlers’ knowledge of hygiene. This improvement is crucial for ensuring the implementation of safe and hygienic food handling practices within hospital settings, thereby safeguarding patient health against foodborne diseases.